2010
DOI: 10.1080/00150191003744476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Firing Temperatures on Phase and Morphology Evolution of CaZrO3Ceramics Synthesized Using the Combustion Technique

Abstract: The effects of calcination temperatures (900-1400 • C) and sintering temperatures (1400-1650 • C) on phase and morphology evolution of perovskite CaZrO 3 ceramics were studied. The results obtained from DTA-TGA analysis were used to determine the processed conditions of various calcination temperatures. The highest purity of the orthorhombic perovskite phase was obtained from powder calcined at 1200 • C and the pure phase was detected in sintered ceramic samples below 1650 • C. The SEM results showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…The densification mechanisms during treatment corresponded to the grain growth, especially during the final stage of sintering. The expansion of trapped gases in the pores assembled and grew as a result of the grain growth [15,17]. This result agreed with the microstructure and XRD result of the ceramic and proved that high density of CCTO ceramics could be prepared by the combustion technique.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The densification mechanisms during treatment corresponded to the grain growth, especially during the final stage of sintering. The expansion of trapped gases in the pores assembled and grew as a result of the grain growth [15,17]. This result agreed with the microstructure and XRD result of the ceramic and proved that high density of CCTO ceramics could be prepared by the combustion technique.…”
Section: Resultssupporting
confidence: 89%
“…The reaction can occur easily in a liquid system because the diffusion coefficient is higher than in a solid medium [17][18]. The obtained ceramics have a high density and excellent electrical properties with a low firing temperature and a short soaking time [15][16][17][18]. Furthermore, the preparation and characterization of CaCu 3 Ti 4 O 12 (CCTO) ceramics, using the combustion technique, have not been reported in the literature.…”
Section: /[1038]mentioning
confidence: 97%
See 1 more Smart Citation
“…6. It could be observed that the mean grain size of CaZrO 3 is stabilized around 74 nm either in the fresh Ca 8 Zr 2 or in its carbonated products after the different cycles for its good phase stability [51]. Different from the stable grain size for CaZrO 3 , a little increase in the mean grain size of the carbonated product CaCO 3 is observed from 43.3 nm after the 5th cycle to 45.5 nm after the 18th cycle mainly because the formed CaCO 3 owns the low resistance to sintering for its lower Tammann temperature of only 533°C, as compared to that of CaO as 1313°C [4] and thus much inferior to sintering, which incurs the agglomeration of the newly formed CaCO 3 grains and further growth in their grain size [26].…”
Section: Phase Analysis Of Sgcs-made Cao Sorbent Over the Cycles By Xrdmentioning
confidence: 96%
“…5. The SGCS-made Ca 8 Zr 2 is found to consist of CaO and CaZrO 3 instead of ZrO 2 , where CaZrO 3 is easily formed by the interaction of CaO with ZrO 2 and displayed great superiority in contrast to ZrO 2 for its high melting temperature, thermal and chemical stability, good thermal shock resistance and low thermal expansion coefficient [46,51,52]. Besides the binder CaZrO 3 and the carbonated product CaCO 3 , a little CaO is left and does not react with CO 2 .…”
Section: Phase Analysis Of Sgcs-made Cao Sorbent Over the Cycles By Xrdmentioning
confidence: 99%